Processing and structural characterization of Si-based carbothermal derivatives of rice husk. Issue 1 (1st January 2018) - Adediran, Adeolu Adesoji; Alaneme, Kenneth Kanayo; Oladele, Isiaka Oluwole; Akinlabi, Esther Titilayo
Abstract: The processing and structural characterization of Si-based carbothermal derivatives of rice husk (RH) was investigated. RH, an agro-waste, was used as starting material in a single-stage processing route to produce Si-based refractory compounds via carbothermal treatment. The processing was carried out at different temperatures windows (900–1, 900°C) at 10°C/min heating range in a controlled atmosphere. The functional groups of the reaction products were analyzed using Fourier transform infrared spectroscopy. The crystalline and amorphous phases were identified by X-ray diffractometer (XRD), while the morphological features were examined by scanning electron microscopy. It was observed that the major functional groups present after carbothermal treatment of RH are OH − (hydroxyl), Si–O–Si (siloxane), and Si–C groups. However, polytypes of silicon carbide (SiC) such as 3C-SiC (C = cubic), hexagonal symmetry 6H-SiC, and mixes of 3C-SiC, 2H-SiC, and 4H-SiC were various polytypes of SiC observed for different processing temperatures adopted. The SiC made up between 63 and 74 wt.% of the crystalline phases was identified by XRD from the process. Hence, the carbothermal treatment explored showed evidence of viability for production of Si-based refractory compounds which can serve as reinforcement in the development of metal matrix composites.